THE ANALYS OF FEATURE CHANGES IN STRUCTURE OF ALLOYING OF AL25 AFTER ELECTRO-SPARK BY TRANSITIONAL METALS - Лабунець, В. Ф.; Городиський, О. А. (Science-based technologies, 2010)
In this article is given the analysis of the modern state of using of methods of plotting coverages on aluminium alloys. Affter the process of alloying of Al25 by transitional metals were determined changes in the structure of local zones and microhardness. It was shown that alloying by transitional metals helps to increase in more than 3 times the hardness of the outgoing material.